Effects of operating conditions and pre-densification on the torrefaction products of sorghum straw - Liu, Xuanzuo; Yao, Zonglu; Cong, Hongbin; Zhao, Lixin; Huo, Lili; Song, Jinchun (International Journal of Agricultural and Biological Engineering, 2020)
The effects of operating conditions and pre-densification on the torrefaction performance parameters and the properties of the torrefied sorghum straw were studied. A full-factor experiment was performed on a fixed tube furnace, in which sorghum straw powder and pellets were heated to 230°C, 260°C, 280°C and 300°C at 2.5°C/min, 5°C/min and 7.5°C/min, respectively. The pyrolysis characteristics of the sorghum straw torrefied under various operating conditions were complemented by thermogravimetric analysis. It was observed that the high temperature led to the high calorific value of the torrefied sorghum straw with an acceptable mass and energy yield. The sorghum straw torrefied at a temperature above 280°C had a higher heating value (HHV) that was comparable to that of the low rank coal while maintaining its energy yield above 85%. The results suggested that temperature was an important factor determining the properties of the torrefied products, and the heating rate would affect the internal temperature of the torrefied biomass by affecting the heat transfer during the torrefaction. The energy densification index of the pellets decreased uniformly as the heating rate increased proportionally, indicating that pre-densification can be used as a potential method to solve the heat transfer delay in the fixed reactors at high heating rates, especially for high temperatures.Keywords: torrefaction, pre-densification, pyrolysis characteristics, operating condition, sorghum straw, heat transferDOI: 10.25165/j.ijabe.20201304.5517Citation: Liu X Z, Yao Z L, Cong H B, Zhao L X, Huo L L, Song J C. Effects of operating conditions and pre-densification on the torrefaction products of sorghum straw. Int J Agric & Biol Eng, 2020; 13(4): 219–225.